2012
DOI: 10.4103/0975-7406.92725
|View full text |Cite
|
Sign up to set email alerts
|

Current approaches toward production of secondary plant metabolites

Abstract: Plants are the tremendous source for the discovery of new products with medicinal importance in drug development. Today several distinct chemicals derived from plants are important drugs, which are currently used in one or more countries in the world. Secondary metabolites are economically important as drugs, flavor and fragrances, dye and pigments, pesticides, and food additives. Many of the drugs sold today are simple synthetic modifications or copies of the naturally obtained substances. The evolving commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
281
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 543 publications
(293 citation statements)
references
References 59 publications
(67 reference statements)
1
281
0
11
Order By: Relevance
“…In recent years, secondary metabolites, pigments of microorganisms, and their biosynthesis pathways have been the subject of much attention (13). Scientifically, fermentation of microorganisms, such as fungi and bacteria could be a valuable source for the production of colored substances, thus looking for environmentally friendly renewable resources is an essential need for the production of colored substances (14).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, secondary metabolites, pigments of microorganisms, and their biosynthesis pathways have been the subject of much attention (13). Scientifically, fermentation of microorganisms, such as fungi and bacteria could be a valuable source for the production of colored substances, thus looking for environmentally friendly renewable resources is an essential need for the production of colored substances (14).…”
Section: Discussionmentioning
confidence: 99%
“…Yendo et al (2010) and Karuppusamy (2009) assert that some strategies have been used for improving the production of metabolites in cultures based on the principle of increasing the yield of the metabolite of interest. Hussain et al (2012) report that the use of calluses has great potential in the production of a variety of secondary metabolites because the production becomes more reliable, simple and predictable.…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary phytochemical screening tests may be separation of pharmacologically active chemical compounds 18 . Secondary metabolites are economically important as drugs, flavor and fragrances, dye and pigments, pesticides, and food additives 19,20 . The plant under study showed presence of various secondary metabolites with important biological activities ( Table 1).…”
Section: Resultsmentioning
confidence: 99%